ANALISIS KESALAHAN SISWA KELAS X SMA DALAM MENYELESAIKAN SOAL HOTS PERSAMAAN EKSPONEN DAN SCAFFOLDING-NYA [ERROR ANALYSIS OF GRADE 10 STUDENTS IN SOLVING HOTS QUESTIONS ON EXPONENTIAL EQUATIONS AND THEIR SCAFFOLDING] - Indayani, Nunik; Hidayanto, Erry; Sisworo, Sisworo (JOHME: Journal of Holistic Mathematics Education, 2024)
The aim of this research is to describe the mistakes made by grade 10 students at SMA Hati Bilingual Boarding School Probolinggo in solving HOTS questions on exponential equations and their scaffolding. This study used qualitative research methods. The subjects of this research were four students with different types of errors. The results of the research show that the basic error type is mostly made because students do not understand the meaning and concept of solving problems. Apart from that, students also make other types of errors, namely the appropriate error type because students cannot solve the exponential form of the equation, the missing information type because students cannot continue the solving process, and the partial insight type because students make mistakes in calculations. The research results also show that the scaffolding process for students with basic error types takes longer than for students with other types of errors. It is hoped that future research will be able to analyze student errors on HOTS questions using other theories or procedures in order to help students overcome their mistakes and minimize errors when solving HOTS questions.BAHASA INDONESIA ABSTRACT: Tujuan penelitian ini untuk menjelaskan kesalahan siswa kelas X di SMA Hati Bilingual Boarding School Probolinggo dalam menyelesaikan soal HOTS persamaan eksponen serta scaffoldingnya. Penelitian ini menggunakan metode penelitian kualitatif. Subjek penelitian ini adalah empat siswa dengan tipe kesalahan berbeda. Hasil penelitian menunjukkan bahwa kesalahan tipe basic error paling banyak dilakukan karena siswa tidak memahami maksud dan konsep untuk menyelesaikan soal. Selain itu, siswa juga melakukan tipe kesalahan lain yaitu tipe appropriate error karena siswa tidak dapat menyelesaikan bentuk persamaan eksponen, tipe missing information karena siswa tidak dapat melanjutkan proses penyelesaian, serta tipe partial insight karena siswa salah dalam perhitungan. Hasil penelitian juga menunjukkan bahwa proses scaffolding untuk siswa dengan tipe kesalahan basic error berlangsung lebih lama dibandingkan siswa dengan tipe kesalahan lain. Penelitian selanjutnya diharapkan dapat melakukan analisis kesalahan siswa pada soal HOTS dengan teori atau prosedur lain, sehingga dapat membantu siswa mengatasi kesalahannya dan meminimalisir kesalahan ketika memecahkan soal HOTS.